(untitled) (Research, Society and Development, 2021)
The natural regrowth of Axonopus aureus in native pasture of Roraima´s savannas was evaluate, during early rainy period. The experimental design was a completely randomized, with four replications. The treatments consisted of four pasture rest periods (14, 28, 42 and 56 days after beginning of the rainy period). Evaluations were carry out during the period of June to August of 2016. The parameters measured were dry matter (DM) yields and grass morphogenetic and structural characteristics. The green and total DM, number of tillers plant-1, number of axillary tillers plant-1, number of live tillers plant-1, number of live leaves tiller-1 and leaf area index were directly proportional to rest periods. The leaf appearance and elongation rate were negatively affect by rest periods, while the dead DM was not affect by rest periods. Considering the low green DM availability of A. aureus, its recommends the utilization of some management practice, preferentially grazing or mowing, to remove the dead DM with low nutrition value and permit a grass vigorous regrowth in the beginning of the rainy period.